Ultraviolet disinfection for controlling crown rot disease and retaining quality of Musa AAA Berangan fruit - Sheikh Mohamed, Nuratika Tamimi (2017)
Crown rot, caused by pathogen complexes, is one of the main diseases affecting banana fruit. A study was conducted to evaluate the potential of ultraviolet C (UVC), an environmentally friendly technology, to control crown rot disease and the impacts on postharvest quality of banana fruit during ripening. UVC irradiation is known for its efficient germicidal effect and potentially to be used as an alternative strategy to replace fungicide. Three pathogenic fungi identified as Lasiodiplodia theobromae, Colletotrichum musae and Fusarium equiseti were isolated from decaying crown surfaces of Musa AAA 'Berangan' banana, a Malaysian local cultivar. These three isolates were confirmed their species level based on cultural, morphological and nucleotide sequences of internal transcribed spacer region (ITS). Pathogenicity tests showed that inoculation with L. theobromae and combination of C. musae + F. equiseti + L. theobromae gave the maximum disease expression as compared to the individual isolates of C. musae and F. equiseti. The results of an increase eight steps UVC doses from 0.01 to 0.30 kJ m-2 show random increases and decreases in fungal growth of all fungi species tested. In percentage inhibition radial growth, 0.3 kJ m-2 was the best for F. equiseti, both 0.2 and 0.3 kJ m-2 doses were the best for L. theobromae, while 0.01 and 0.60 kJ m-2 effectively inhibited the C. musae radial growth. Meanwhile, 0.015 kJ m-2 UVC was effective in restraining the conidial germination and sporulation of these fungi. The effect of UVC on area under disease progress curve (AUDPC) indicated that the highest AUDPC of 77.5 unit2 was recorded in negative control fruit, whereas, fruit treated with 0.30 kJ m-2 showed the lowest AUDPC value of 38.1 unit2. However, the application of UVC irradiation dose on banana fruit was found limited due to the adverse effect of higher doses that causing browning discoloration on fruit peel. All the applied doses including 0.02 to 0.05 kJ m-2 showed browning scores that corresponding to 40 to 60% peel browning, whereas, fruit treated with 0.01 kJ m-2 UVC showed a much lower of browning score by the end of the ripening period. UVC irradiation at 0.01 kJ m-2 could be considered as the optimum dose for Berangan banana, as it synergistically reduced the disease severity by 46.25% without causing browning on the fruit peel. In contrast, UVC irradiation at 0.05 kJ m-2 was found caused peel browning and induced rapid changes in colour, soluble solids concentration and pH of the fruit. The severity of crown rot disease was lower in banana hands irradiated with UVC at 24 h after artificial inoculation compared to those irradiated 24 h before inoculation. Application of low dose UVC irradiation was able to elicit some desirable responses in banana such as induction of peroxidases, accumulation of lignins, formation of cell wall apposition and phenol storing cells to improve their defense against fungi. This study suggested that UVC irradiation at low dose is promising and environmentally friendly to be used as the alternative method for fungicides treatment of banana at postharvest.